Strategi digital marketing dalam menumbuhkan startup jastip Indonesia-Jepang - Puspo Dewi Dirgantari; Ratih Hurriyati; Sulastri Sulastri; Masharyono Masharyono; Ratu Dintha Insyani Zukhruf Firdausi Sulaksana; Yusuf Murtadlo Hidayat; Bambang Widjadjanta (Universitas Pendidikan Indonesia, 2022)
The process of distributing products and services has changed significantly in recent years, consumers are now using online means and are increasingly looking for online channels to research and buy the products or services they need, this condition has sparked the birth of the Jasa Titip (Jastip) business phenomenon which is becoming known to the public in Indonesia since 2014 until now. Jastip Japan is one of the most popular, seen from the unique, value for money, high tech, and high quality goods that make Japan a paradise for entrusted service businessmen. Delivery services in Japan are also mushrooming, as can be seen from the many availability of delivery services in Japan. However, the Covid-19 pandemic which has not subsided has made the lives of Indonesian citizens in Japan even worse, and some Indonesian citizens have even been locked up or laid off. Jastip business people are usually hampered by the lack of knowledge about digital marketing, so it is necessary to carry out digital marketing training by utilizing the internet and social media in developing a Jastip business. The purpose of this community service activity is to increase competence and/or assistance needed, especially in the field of digital marketing to optimize Jastip business for PMIs in Japan.